Detection of Multiple Nitroaromatic Explosives via Formation of a Janowsky Complex and SERS - Milligan, Kirsty (Anal Chem, 2020)
[Image: see text] Military-grade explosives such as 2,4,6-trinitroluene (TNT) are still a major worldwide concern in terms of terror threat and environmental impact. The most common methods currently employed for the detection of explosives involve colorimetric tests, which are known to be rapid and portable; however, they often display false positives and lack sensitivity. Other methods used include ion mobility mass spectrometry, gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS), which despite producing more reliable results often require large, expensive instrumentation and specially trained staff. Here we demonstrate an alternative approach that utilizes the formation of a colored Janowsky complex with nitroaromatic explosives through reaction of the enolate ion of 3-mercapto-2-butanone. The colored complex is formed rapidly and can then be detected sensitively using surface-enhanced Raman scattering (SERS). We demonstrate that SERS can be used as a quick, sensitive, and selective technique for the detection of 2,4,6-trinitrotoluene (TNT), hexanitrostillbene (HNS), and 2,4,6-trinitrophenylmethylnitramine (tetryl) with a detection limit of 6.81 ng mL(–1) achieved for TNT, 17.2 ng mL(–1) for tetryl, and 135.1 ng mL(–1) for HNS. This method of detection also requires minimal sample preparation, can be done in a solution-based format, and utilizes the same precursor reagents for complex formation with each of the explosives which can then be identified due to the specificity of the unique SERS response obtained. We demonstrate the ability to simultaneously identify three explosive compounds within a total analysis time of 10 min. This method of detection shows promise for the development of rapid and portable SERS-based assays which can be utilized in the field in order to achieve reliable and quantitative detection.